2012
DOI: 10.1371/journal.pone.0030483
|View full text |Cite
|
Sign up to set email alerts
|

TEPITOPEpan: Extending TEPITOPE for Peptide Binding Prediction Covering over 700 HLA-DR Molecules

Abstract: MotivationAccurate identification of peptides binding to specific Major Histocompatibility Complex Class II (MHC-II) molecules is of great importance for elucidating the underlying mechanism of immune recognition, as well as for developing effective epitope-based vaccines and promising immunotherapies for many severe diseases. Due to extreme polymorphism of MHC-II alleles and the high cost of biochemical experiments, the development of computational methods for accurate prediction of binding peptides of MHC-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 35 publications
0
98
1
Order By: Relevance
“…The loading of a particular peptide onto an HLA class II molecule is dependent strictly on the characteristic of the peptide-binding groove of the molecules. [32][33][34] In HLA-DR molecules, pockets P1, P4, P6, P7, and P9 are present within the binding groove. 33 Among the 5 pockets, the amino acid epitopes in pockets 4, 6, and 7 seem to have a role in the susceptibility of sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…The loading of a particular peptide onto an HLA class II molecule is dependent strictly on the characteristic of the peptide-binding groove of the molecules. [32][33][34] In HLA-DR molecules, pockets P1, P4, P6, P7, and P9 are present within the binding groove. 33 Among the 5 pockets, the amino acid epitopes in pockets 4, 6, and 7 seem to have a role in the susceptibility of sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…immunization poses a risk of antigen delivery to the central nervous system and recent studies have indicated that sublingual vaccination is a safer route (39). Further development of an epitope-based vaccine against coccidioidomycosis should both help to elucidate underlying mechanisms of immune recognition and yield a potentially promising protective reagent against this respiratory disease (53).…”
Section: Discussionmentioning
confidence: 99%
“…Promiscuous peptides binding to multiple HLA class II molecules were selected. The analysis was made by using the TEPITOPE [37] software, with a threshold of 5% for the most common human HLA-DR alleles [DR1, DR3, DR4, DR7, DR8, DR5 and DR2] among Caucasian population [21], and covering a large proportion of the peptides that bind human HLA.…”
Section: T-cell Epitopes Identification and Analysismentioning
confidence: 99%